Implementasi Kompetensi Kepribadian Guru Dalam Membangun Kemandirian Peserta Didik - Fitri Nurbani; Awang Kustiawan; Dadi Dadi (PT. ALHAFI BERKAH INDONESIA, 2023)
The teacher's personality competence is closely related to the personality development of students. Teachers with strong personalities will have an impact on students both in the perspective of a good teacher's image and in direct influence in the form of the teacher's efforts to carry out ideal learning. What is interesting is the extent to which the teacher's personality competence has an impact on the development of student independence. This study used descriptive qualitative method. The subjects in this study were teachers, students and school principals of SMPN 5 Malangbong, Garut Regency. To obtain data used techniques of observation, interviews, and documentation. The collected data were analyzed through a sequence of data reduction, data presentation, drawing conclusions, and triangulation. The results showed that the majority of SMPN 5 Malangbong teachers in Garut district already had teacher personality competencies and implemented them in learning activities. The personality of the teacher succeeded in developing the independence of students, especially self-confidence, responsibility and initiative. There were several obstacles found in this study, namely students did not want to open up, did not have the desire to change, and could not imitate what the teacher did. This condition requires further efforts to provide opportunities for students to develop according to their age. It was also found that several teachers did not have complete teacher personality competencies so that they were suspected of influencing the slow adaptability of students in learning. Other obstacles are teacher communication with parents that is not intense, the distance where students live far from the school, parents' human resources, and economic factors.